2011
DOI: 10.5194/acp-11-3743-2011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of rainwater at Maldives Climate Observatory at Hanimaadhoo (MCOH)

Abstract: Abstract. Water-soluble inorganic components in rain deposited at the Maldives Climate Observatory Hanimaadhoo (MCOH) were examined to determine seasonality and possible source regions. The study, which is part of the Atmospheric Brown Cloud (ABC) project, covers the period

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Quality checks of the IC-analyses were performed with both internal and external reference samples (Das et al, 2011) <6%, <0.1%, >0.2%, <0.2%, and 0% of the sample, respectively. Additional procedural information is given in Engstr€ om and .…”
Section: Inorganic Compounds Msa and Oxalic Acidmentioning
confidence: 99%
“…Quality checks of the IC-analyses were performed with both internal and external reference samples (Das et al, 2011) <6%, <0.1%, >0.2%, <0.2%, and 0% of the sample, respectively. Additional procedural information is given in Engstr€ om and .…”
Section: Inorganic Compounds Msa and Oxalic Acidmentioning
confidence: 99%
“…However, there have been no systematic, long-term measurements of rainwater chemistry have been made over Indgo Gangetic Plains (IGP) region to date (Satsangi et al, 1998a, b;Das et al, 2005;Singh et al, 2007a;Tiwari et al, 2007;Das et al, 2010;Shukla and Sharma, 2010;Das et al, 2011;Tiwari et al, 2012;references therein). The IGP supports nearly 70% of India's population and is one of the highly polluted and industrialized regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the studies of precipitation chemistry in South Asian region especially in India have been performed (Rao et al, 1992;Granat et al, 2002;Kulshrestha et al, 2003;Safai et al, 2004;Kulshrestha et al, 2005;Momin et al, 2005;Mouli et al, 2005;Tiwari et al, 2007;Rastogi and Sarin, 2007;Salve et al, 2008;Budhavant et al, 2009;Safai et al, 2010;Shukla and Sharma, 2010;Budhavant et al, 2011, Das et al, 2011Salve et al, 2011;Tiwari et al, 2011Tiwari et al, , 2012Budhavant et al, 2014; references therein). However, there have been no systematic, long-term measurements of rainwater chemistry have been made over Indgo Gangetic Plains (IGP) region to date (Satsangi et al, 1998a, b;Das et al, 2005;Singh et al, 2007a;Tiwari et al, 2007;Das et al, 2010;Shukla and Sharma, 2010;Das et al, 2011;Tiwari et al, 2012;references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies reported from Maldives are part of Atmospheric Brown Cloud (ABC) project as MCOH Climate Observatory is located at Hanimaadhoo Island. Transport of pollutants up to MCOH has been reported by Das and coworkers [68]. They have used airmass trajectories to interpret the water soluble inorganic components in rain deposited at MCOH to find out seasonality and possible source regions.…”
Section: Maldivesmentioning
confidence: 99%